MDR PULMONARY TB + HIV Stage 3 + SUSPECTED RIGHT LUNG TUMOR - Pakpahan, Edwin Anto; Hilmi, Izzatus; Ulfiani, Dede; Putri, Nabilah Triana; Kurnia, Wina Cindy; Pohan, Muhammad Alwi (Universitas Methodist Indonesia, 2023)
Acquired Immunodeficiency Syndrome is a collection of symptoms and infections or syndromes that arise due to damage to the human immune system due to infection with the Human Immunodeficiency Virus (HIV). HIV is a virus that weakens immunity in the human body. Pulmonary tuberculosis (TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis (M. Tb). Tuberculosis is the most common opportunistic infection in people with HIV/AIDS (PLWHA) in Indonesia, HIV infection facilitates Mycobacterium tuberculosis infection. Tumors are abnormal lumps in the body, which can be benign or malignant, which are usually caused by malignancy or infection. Malignancy is a group of diseases in which the cells spread abnormally and grow uncontrollably.Hypercoagulation is a blood coagulation disorder, namely a shift in hemostatic balance due to an increase in procoagulant factors. This tends to cause a thrombus. The coagulation process is influenced by inhibitory factors that maintain the clotting status of a thrombus. Purpose: The purpose of this writing is to discuss the disease regardingHIV + MDR Pulmonary TB + Suspected Right Lung Tumor + Hypercoagulabilityfrom definition to nutritional management so that patients can be treated properly.